Solarization for Pest Management in Florida - Romy Krueger; Robert McSorley (EDIS)
ENY-902, a 9-page illustrated fact sheet by Romy Krueger and Robert McSorley, describes this soil management practice that is typically carried out during the warm summer months to benefit crops grown in the following fall — how it works, technical advice, affected organisms, integrating soil fertility, and considerations/drawbacks. Includes references. Published by the UF Department of Entomology and Nematology, July 2009.